Makna Motivasi dalam Video Klip Lagu “Teramini Ghea Indrawari” (Analisis Semiotika Jhon Fiske) - Syarafi Dwi Mansuri; Iin Soraya; Sari Ekowati (Tamilis Synex: Multidimensional Collaboration, 2024)
With Gen Z's higher level of awareness of mental health, many of them are trying to provide motivation to themselves and others, especially those in the same generation as them. There are many motivations for what they do, one of which is by listening to songs or watching video clips that relate to them. In this era, apart from listening to songs or watching MVs, many of them are creating songs about mental health. This can be proven by the many motivational songs related to mental health on social media. The aim of this research is to find out the meaning of motivation in Ghea Indrawari's song "Teramini". This research is qualitative research using John Fiske's semiotic analysis method which consists of three levels, namely the reality level, representation level and ideology level. Data was obtained through the video clip file for the song "Teramini" Ghea Indrawari. The research results show that every human being needs motivation to survive. Motivation has an important influence in a person's life, even through video clips and songs, people can have motivation. Video clips have other functions, apart from promoting a singer's work, video clips can be a means and infrastructure for someone to provide motivation.